Dynamics of convective organization in African easterly waves observed during the NAMMA and CPEX-CV field campaigns - Colón-Burgos, Delián, author; Bell, Michael M., advisor; Maloney, Eric, committee member; Davenport, Frances, committee member (Colorado State University. Libraries, 2025)
The mechanisms that govern the organization of moist convection in weakly rotating flows such as tropical easterly waves are not fully understood. In this study we aim to better understand the dynamical processes that govern the convective organization at the meso-alpha scale, including the location, and intensity of deep convection, using NASA airborne field campaign and satellite observations. We employ a 3D variational analysis technique called SAMURAI in a vortex-centric approach, integrating ERA5 reanalysis and research aircraft observations of 20 African easterly wave (AEW) cases collected during NAMMA in 2006 and CPEX-CV in 2022. The SAMURAI analyses are centered on a potential vorticity (PV) centroid and show a low-level wave relative circulation across cases. Convection is classified from satellite imagery into three classes of shallow/moderate and deep to obtain a frequency of the occurrence relative to the PV centroid location. We find four clusters of organized deep convection denoted as minimal deep, southern, southwestern, and widespread, with the southwestern and widespread clusters associated with the greatest magnitudes of frequency. Results from a composite analysis reveal high PV and relative humidity (RH) at mid-levels were approximately co-located with the regions of low-level convergence and more frequent deep convection, particularly for the southwestern and widespread clusters. Waves with a higher frequency of deep convection are characterized by stronger PV and higher RH at mid-levels compared to waves with a lower frequency of deep convection. Further research is recommended to explore these relationships temporally to better determine the role of cause and effect between the PV and RH and deep convective organization.
Keywords: field campaigns; tropical convection; potential vorticity; African easterly waves